Move : AI-powered strategy for a fast world - Lewko, Tim (Routledge, 2026)
Developed by Tim Lewko, a 25-year strategy veteran, MOVE shows leaders how to embed artificial intelligence (AI) directly into the strategy process and validate strategic bets, pressure-test assumptions, and adapt faster than the competition - all while maintaining control over final decisions. Traditional strategy frameworks cannot keep up with trade wars, supply chain disruptions, and shifting consumer behaviour, and leaders can no longer afford to wait for annual planning cycles or lengthy strategy retreats.MOVE responds to this rapid change by simplifying strategy into a clear, repeatable system of seven essential tools - all powered by AI to accelerate decision-making and execution. It's a practical, leadership-owned operating system that aligns strategic assumptions, project prioritization, and quarterly execution cycles. Through examples, this book reveals how AI can power real-time data analysis, surface critical indicators that signal when a strategic bet is veering off-course, and show when emerging threats require immediate attention. In a rapidly changing world, MOVE is a key tool for senior executives, business leaders, board members, CEOs, Presidents, and P&L owners to regain control across the entire execution cycle.
Keywords: Artificial intelligence -- Business applications.; Strategic planning.; elektronické knihy; electronic books